Membangun Kesadaran Remaja melalui Kegiatan Penyuluhan untuk Desa Ramah Perempuan dan Anak : Building Youth Awareness through Outreach Activities for Women and Child-Friendly Villages - Mashitoh, Aristawati; Nisa , Siti Nazilatun; Wahyuningsih, Nadia Destiana; Irsyad, Mohamad (Edujavare Publishing, 2025)
Juvenile delinquency is a social phenomenon that arises due to the complex interaction between internal and external factors in an individual's life. The phenomenon of juvenile delinquency is a serious concern because its impact is not only felt by individuals, but also by families, schools, and communities in Kalikebo Village, Dukuh Karakan and Brijokidul. This study aims to determine the factors causing juvenile delinquency and the forms of preventive efforts that can be carried out by families, schools, and the community regarding the dangers of juvenile delinquency in Kalikebo Village, especially in Dukuh Karakan and Brijokidul. The method used is descriptive qualitative, with data collection through interviews and observations. Research informants consisted of adolescents involved in delinquency, parents, and related parties in the community. The results of the study indicate that the factors causing juvenile delinquency include internal factors such as identity crises and weak self-control, as well as external factors such as lack of communication within the family, environmental influences, and peers. Positive activities such as volleyball tournaments and mutual cooperation held by KKN UIN Raden Mas Said Surakarta students have proven effective in preventing juvenile delinquency by channeling energy, forming character, increasing awareness, and strengthening social relationships. This study recommends the need for collaboration between families, schools, and communities in creating an environment that supports positive adolescent development.